ANALYZING ORGANIZATIONAL COMMITMENT IN BANKING: THE IMPACT OF WORK-LIFE BALANCE, ORGANIZATIONAL SUPPORT, AND OPERATIONAL WORKLOAD - Aziz Asri Mufti; Suarmanayasa I Nengah; Telagawathi Ni Luh Wayan Sayang (SOSIOEDUKASI, 2026)
This research aims to analyse the influence of work-life balance, perceived organizational support, and workload on organizational commitment at PT. Bank Rakyat Indonesia (Persero) Tbk., Gatot Subroto Branch Office, Denpasar. The study employed a quantitative causal research design to examine the relationships between these variables. A census sampling technique was utilized, involving the entire population of 133 permanent employees. Data were collected through structured questionnaires using a 5-point Likert scale and analysed using multiple linear regression, partial t-tests, and simultaneous F-test via SPSS 25. The results demonstrate that work-life balance and perceived organizational support each have a positive and significant partial effect on organizational commitment. Conversely, workload has a negative and significant influence, indicating that excessive task demands can drastically reduce employee loyalty. Simultaneously, these three variables significantly influence commitment with an F-value of 163.809 (p < 0.05), accounting for 79.2% of the commitment variance. This study provides a significant contribution by validating "Social Exchange Theory" and the "Three-Component Model of Commitment" within the Indonesian banking context, proving that the integration of organizational welfare and balanced task demands is a more dominant predictor of success than traditional operational targets. Furthermore, it highlights the management's evolving role in mitigating burnout and maintaining psychological ties during banking transformations.The study concludes that work-life balance, perceived organizational support, and workload serve as vital predictors of employee retention in the banking sector. These findings suggest that management should prioritize rational evaluations of operational targets and strengthen organizational support policies to maintain human resource stability and competitive advantage.